ANALISIS PELAKSANAAN PEMBAGIAN HARTA WARIS BAGI PARA AHLI WARIS BEDA AGAMA DALAM STUDI KASUS PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR 239/Pdt.G/2015/PN.JKT.PST - tika bonet; Mulati Mulati (Fakultas Hukum Universitas Tarumanagara, 2021)
Inheritance law in general can occur or be implemented if there is death or divorce. There is no inheritance law in Indonesian. There is only one law that can determine the position of one's inheritance. Inheritance law is divided into three types in Indonesia, which are Traditional, Western and Islamic. Muslims who follow the provisions of the existing regulations in the Compilation of Islamic Law. Analysis of the implementation of the distribution of inheritance for heirs of different religions in the Study of Central Jakarta District Court Decision No. 239 / Pdt.G / 2015 / Pn.JKT.PST. This knowledge is very important and useful to learn so that there are no mistakes in the distribution of assets and can be fairly distributed. Where all rights and obligations can be fulfilled. If someone is married in Islam then they have to use Islamic Law Compilation because in the division of inheritance that is regulated in the West there is no difference between men and women in doing the distribution of inheritance. The research method used is normative legal research supported by the results of interviews. The results of the analysis in this study should be that the Judge goes deeper into the suit and the Advocate must be more careful in entering the lawsuit. Everything received by the Plaintiff is not in accordance with the provisions it should.